The Rise of the Avant-Gardes 1848-1918 : A Transnational History - Joyeux-Prunel, Béatrice, (Avant-Garde Critical Studies ;, 2026)
Why did modern painting flourish in Paris, Vienna, or Brussels but stall in London or Madrid? What propelled some avant-gardes to global fame while others vanished? This book takes you inside modern art's explosive rise between 1848 and 1918, revealing how artists navigated nationalism, markets, elite networks, and public demands to invent new ways of making-and living-art. Forget the myth of isolated geniuses. Here, avant-gardes cross borders via dealers, journals, exhibitions, and exiles. Follow their journey from Paris to Moscow, Barcelona, and New York through alliances, rivalries, and migrations. Richly illustrated with artworks, maps, and charts, this is art history reimagined-transnational, social, and vividly alive.